2020
DOI: 10.1371/journal.pone.0228847
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy of direct acting antiviral therapies in patients with HIV/HCV

Abstract: The advent of direct-acting antiviral (DAA) therapies has dramatically transformed HCV treatment, with most recent trials demonstrating high efficacy rates (>90%) across all genotypes and special populations, including patients with HIV/HCV coinfection. The efficacy rates of HCV treatment are nearly identical between patients with HCV monofection and patients with HIV/HCV coinfection; however, there are limited studies to compare real-world efficacy with efficacy observed in clinical trials. Using a database f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
4
20
3
Order By: Relevance
“…52 Deaths from complications of HCV infection such as end-stage liver disease or HCC exhibited a longer and later peak, 23,35 perhaps because of the time taken to develop and succumb to these complications 53,54 or the development of highly effective antiviral therapies against HCV. 55 Two studies reported higher mortality rates when PwH were coinfected with HIV and HCV. 25,35 HIV/HCV coinfection accelerates the progression of hepatic disease as the individual becomes significantly immunocompromised.…”
Section: Primary Cause Of Death Changed Over Timementioning
confidence: 99%
“…52 Deaths from complications of HCV infection such as end-stage liver disease or HCC exhibited a longer and later peak, 23,35 perhaps because of the time taken to develop and succumb to these complications 53,54 or the development of highly effective antiviral therapies against HCV. 55 Two studies reported higher mortality rates when PwH were coinfected with HIV and HCV. 25,35 HIV/HCV coinfection accelerates the progression of hepatic disease as the individual becomes significantly immunocompromised.…”
Section: Primary Cause Of Death Changed Over Timementioning
confidence: 99%
“…Nowadays, interferon‐free direct acting antivirals (DAA) treatment has come to allow successful HCV clearance at a significant rate even in the co‐infected patients. It will be a major challenge for the future to examine whether it is appropriate to increase the rank of MELD score for patients with successful HCV clearance 24 . In conclusion, our study group established DDLT criteria for patients with HIV/HCV co‐infection from blood products and perioperative management, and then promptly included patients eligible for liver transplant to the DD transplantation waiting list and performed DDLT.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection is also more common in MSM coinfected with HIV (3%‐39%) compared with those without (0%‐19%) 49 . Although HCV is more prevalent in HIV‐coinfected individuals, DAA therapy demonstrates similarly high efficacy in this population compared with those without HIV coinfection 50 . Drug‐drug interactions (DDIs) are a potential problem when combining HIV and HCV treatment; however, studies have demonstrated effective and well‐tolerated management of DDIs as long as care providers are aware of the risk 51 …”
Section: Barriers and Challenges To Eliminationmentioning
confidence: 99%